2016
DOI: 10.4038/tare.v19i1.5381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parboiling on minerals and heavy metals of selected Sri Lankan traditional rice varieties grown under organic farming

Abstract: The study was conducted to evaluate the effects of parboiling treatment on the minerals and heavy metals of six Sri Lankan traditional rice varieties; Kalu heenati, Pokkali, Gurusinghe wee, Kahawanu, Sudu murunga and Unakola samba. Metals were determined by using ICP-AES and AAS. Parboiling can be considered as a suitable rice processing method for Pokkali and Kahawanu and not for Kalu heenati and Unakola samba in order to furnish the recommended daily intake of the micronutrients. Un-parboiled Kalu heenati an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, according to the worked done by Kariyawasam and her co-workers [32], this variety consists of 2.1±0.01 mg of Fe, 3.8±0.01 mg of Zn, 0.04±0.0 mg of Mn, 4.52±0.30 mg of K, 1.59±0.20 mg of Mg in 100 g of Sudumurunga rice flour. Hence, all of these nutritious and mineral content may benefit health [32].…”
Section: Sudumurungamentioning
confidence: 92%
See 2 more Smart Citations
“…Also, according to the worked done by Kariyawasam and her co-workers [32], this variety consists of 2.1±0.01 mg of Fe, 3.8±0.01 mg of Zn, 0.04±0.0 mg of Mn, 4.52±0.30 mg of K, 1.59±0.20 mg of Mg in 100 g of Sudumurunga rice flour. Hence, all of these nutritious and mineral content may benefit health [32].…”
Section: Sudumurungamentioning
confidence: 92%
“…The proximate composition of Sudumurunga variety has shown that it contains 11.9±0.1% of moisture, 9.7±0.3% of crude protein, 1.2±0.0 % of crude ash, 2.7±0.0% of crude fat and 73.6±0.1% total carbohydrates, 1.1±0.0% crude fiber in dry basis [30]. Also, according to the worked done by Kariyawasam and her co-workers [32], this variety consists of 2.1±0.01 mg of Fe, 3.8±0.01 mg of Zn, 0.04±0.0 mg of Mn, 4.52±0.30 mg of K, 1.59±0.20 mg of Mg in 100 g of Sudumurunga rice flour. Hence, all of these nutritious and mineral content may benefit health [32].…”
Section: Sudumurungamentioning
confidence: 97%
See 1 more Smart Citation